2017
DOI: 10.21608/ejh.2017.4654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethanol on rat tongue and the possible protective role of royal jelly: Light and scanning electron microscopic study

Abstract: Background: Ethanol is the most commonly used and abused xenobiotic in the world. Royal jelly (RJ) has been considered as an antioxidant that protects against different agents. Aim of the work: This study aimed to investigate the effect of ethanol on the rat tongue and the possible protective role of royal jelly. Material and methods: Twenty five adult male rats were used in this study and were divided into 4 groups. Group I: 10 rats were divided equally into negative and positive controls. Group II: 5 rats re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Scanning electron microscopy (SEM) of nicotine + Royal jelly treated rats revealed marked improvement of the tongue mucosa in the form of regular orientation of the lingual filiform papillae and normal picture of the fungiform papillae, similar results were observed by a previous study that was carried out by SEM that royal jelly caused amelioration of the ethanol damaging effects on the lingual papillae (25) .Royal jelly was proved to have a potential repro-protective action against nicotineinduced sperm abnormalities and embryo-toxicity in mice and protects male mice against nicotine-induced reproductive failure (26) .On the other hand a previous study showed that honey caused marked regeneration of the lingual papillae observed by both light and SEM against the lead-induced lingual atrophy (27) .Bee products are considered to be a potential source of natural antioxidants such as flavonoids, phenolic acids, or terpenoids which are capable of counteracting the effects of oxidative stress underlying the pathogenesis of numerous diseases as well as negative effects of different harmful factors and drugs (8) .…”
Section: Discussionsupporting
confidence: 82%
“…Scanning electron microscopy (SEM) of nicotine + Royal jelly treated rats revealed marked improvement of the tongue mucosa in the form of regular orientation of the lingual filiform papillae and normal picture of the fungiform papillae, similar results were observed by a previous study that was carried out by SEM that royal jelly caused amelioration of the ethanol damaging effects on the lingual papillae (25) .Royal jelly was proved to have a potential repro-protective action against nicotineinduced sperm abnormalities and embryo-toxicity in mice and protects male mice against nicotine-induced reproductive failure (26) .On the other hand a previous study showed that honey caused marked regeneration of the lingual papillae observed by both light and SEM against the lead-induced lingual atrophy (27) .Bee products are considered to be a potential source of natural antioxidants such as flavonoids, phenolic acids, or terpenoids which are capable of counteracting the effects of oxidative stress underlying the pathogenesis of numerous diseases as well as negative effects of different harmful factors and drugs (8) .…”
Section: Discussionsupporting
confidence: 82%
“…Atrophy of papillae was higher in filiform than in fungiform papillae; this is supported by Altayeb & Salem (2017) and may be illustrated by Osman et al (2006) who mentioned that cells of filiform papillae have a high metabolic activity and so any nutritional deficiency, vascular changes or enzymatic disturbance would lead to their atrophy and damage faster and earlier before any other papillae.…”
Section: Discussionmentioning
confidence: 77%
“…These changes were probably due to the oxidative stress induced by the chemotherapeutic agent, 5-FU. The chemotherapeutic agent produced ROS, which can injure several macromolecules in the cell such as proteins, DNA and lipids ( Altayeb & Salem, 2017 ).…”
Section: Resultsmentioning
confidence: 99%